2019
DOI: 10.1155/2019/4909846
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Detection Using Image Segmentation by means of Various Evolutionary Algorithms

Abstract: The objective of this paper is to explore an expedient image segmentation algorithm for medical images to curtail the physicians' interpretation of computer tomography (CT) scan images. Modern medical imaging modalities generate large images that are extremely grim to analyze manually. The consequences of segmentation algorithms rely on the exactitude and convergence time. At this moment, there is a compelling necessity to explore and implement new evolutionary algorithms to solve the problems associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…It is known that radiologists distinguish the benign from malignant nodules by their size, shape, density, and other characteristics [11]. However, CT images are difficult to be analyzed manually, which requires radiologists to have excellent reading skills, especially for the diagnosis of small and isolated pulmonary nodule [12,13]. It is reported that the false positive rate of LDCT screening for lung cancer is as high as 96.4% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that radiologists distinguish the benign from malignant nodules by their size, shape, density, and other characteristics [11]. However, CT images are difficult to be analyzed manually, which requires radiologists to have excellent reading skills, especially for the diagnosis of small and isolated pulmonary nodule [12,13]. It is reported that the false positive rate of LDCT screening for lung cancer is as high as 96.4% [6].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, it is necessary to develop a method that can effectively distinguish benign from malignant CT nodules. At present, many scholars try to extract radiomic features of CT nodules and establish models to achieve the intelligent identification of benign and malignant nodules [12,14,15]. On the other hand, there is an urgent need to seek an auxiliary means, which can enhance the diagnostic efficiency of lung cancer in combination with CT. As we know, tumor markers have been widely used in the detection of lung cancer in recent years, such as progastrin-releasing peptide (ProGRP), vascular endothelial growth factor (VEGF), carcinoembryonic antigen (CEA), cytokeratin 19 fragment (CYFRA21-1) and neuronspecific enolase (NSE) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional methods in clustering analysis are the unsupervised segmentation algorithms, such as k-mean and fuzzy c-mean, where an automatic algorithm separates the given dataset (CT image) into two or more clusters. The procedure involves grouping the data of similar features into one cluster and the data points of dissimilar characteristics into another cluster [21][22].…”
Section: Clustering Methodsmentioning
confidence: 99%
“… FC-Densenet103, Unet, DenseNet, and DenseNet121-FPN. References References [ 137 ] [ 138 ] [ 139 ] [ 140 ] [ 141 ] [ 142 ] [ 143 ] [ 129 ] [ 144 ] [ 145 ] [ 146 ] [ 147 ] [ 148 ] [ 149 ] [ 150 ] [ 151 ] [ 152 ] [ 153 ] [ 154 ] [ 155 ] [ 156 ] [ 157 ] [ 158 ] [ 159 ] [ 160 ] [ 161 ] [ 162 ] [ 163 ] [ 164 ] [ 165 ] Classification Characteristics Characteristics Gray scale feature extraction and ML classifier, and model-based techniques. Resnet-50, CNN, SVM, ResNet101, VGG16, and VGG19.…”
Section: Artificial Intelligence Architectures For Ards Characterizatmentioning
confidence: 99%